THE ABILITY OF THE SECOND YEAR STUDENTS IN ENGLISH PRONOUNS AT MAN 4 BANJAR - fizi (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2024)
The study describes the ability of the second year students in English pronouns at MAN 4 Banjar. The problems of the research are: how is the ability of the second year students in English pronouns at MAN 4 Banjar Banjar and what factors influence the ability. The subjects of the research are 31 second year students at MAN 4 Banjar in academic year 2023 / 2024. While the object of the research are the ability of the second year students in English pronouns at MAN 4 Banjar and factors influence the ability. To collect data the writer applied test, questionnaire, observation, interview, and documentary. The data processing are editing, coding, calculating frequency and tabulating. To analyze the data, is used qualitative descriptive analysis and concluded by inductive method. The result of the research shows that the ability of the second year students in English pronouns at MAN 4 Banjar is averagely in fair category. While description of the influential factors can be identified as follows: students' interest, students' motivation and students' learning activity are quite high that should support students' ability in English pronouns. The English teacher does support students' ability and the teacher factor in this research is in high category. The facility factor is in high category as well. The factor influences the ability of the students in English pronouns.